Development of sugar craving assessment tool and the application of low caloric sweetener in appetite regulation and eating behaviour - Wan Fathin Fariza binti Wan Mahmood (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
Excessive sugar intake has been widely associated with the increased prevalence of obesity and diabetes due to its potential in instigating positive energy balance. Sugar craving, an issue which has yet been explored in our local community, is also postulated to relate to erratic eating behavior, impulsive food intake and binge eating. The initial part of this research aimed to develop and validate a sugar craving assessment tool suitable for Malaysians. Eventually, the Sugar Craving Assessment Tool for Malaysian (MySCAT) was created that has good internal consistency (α = 0.866) and the score was significantly correlated with sugar intake measured via FFQ Sugar (r = 0.332, p <0.01). As opposed to high energy density and palatability of sugar in foods, the low calorie sweeteners (LCS) has been suggested as alternative to sweeten foods but without markedly excessive calories. Stevia has recently been popular as sugar substitute and it is from plant source, hence deemed more acceptable to be consumed by lay person, relative to artificial sweetener like aspartame. Further, we compared the sweetness perception and acceptance of solid and liquid foods containing either sugar, stevia or aspartame. Healthy adults perceived sugar sweeter than both LCS. The replacement of sugar with LCS was acceptable among the subjects. In the subsequent study using different group of subjects, we investigated the association between sugar craving and sweetness perception as well as eating behavior (restraint, emotional and external traits). Results indicate that female, overweight/obese individuals and restraint eaters possessed higher sweetness perception than their counterparts. The final part of this research aimed to compare the effects of sugar, stevia and aspartame consumption on energy compensation, appetite responses (satiety, fullness and desire to eat sweet) and appetite hormones changes (insulin, leptin and ghrelin). The “preload paradigm” method has been used, whereby 3 types of preloads (sugar, stevia and aspartame) were given prior to test meal served as lunch buffet with ad-libitum intake. We found that following LCS preloads, energy intake during test meal was higher (COMPX 45.6% for stevia and 54.1% for aspartame) but total energy intake (preloads + test meal) was significantly higher with LCS consumption. Sugar preload significantly increased leptin the most compared to LCS after 2 hours. There was no significant relationship recorded between sweeteners and their impact on appetitive responses. Conclusively, we had successfully develop a novel method to measure sugar craving among Malaysian and it is useful in the assessment of the risk of excessive sugar intake. In the effort of reducing energy density of food and sugar content, replacement of sugar with stevia, a natural sweetener, is recommended as it proven to reduce total energy intake while maintaining the normal hormonal changes and do not interfere with appetitive responses.